Speciation Of Candida Isolated From Cases Of Vaginal Candidiasis - Guragain, Ankita; Bichchha, Ramesh (Nepal Mediciti Medical Journal, 2021)
Background: Vulvovaginal Candidiasis (VVC) is an exceedingly common mucosal infection of the lower female reproductive tract. Mostly, it is caused by Candida albicans. Yet, non-albicans Candida species are also on the rise. Also, increasing resistance to commonly prescribed antifungal agents is of serious concern. Methodology: High vaginal swabs were collected from clinically suspected cases of VVC from patients attending outpatient department of Obstetrics and Gynecology of NMCTH. The swabs were subjected to microscopic analysis and culture. Germ tube test, CHROMagar, chlyamydospore formation test and sugar assimilation test were applied for identification of the isolated Candida spp. Antifungal susceptibility testing of the isolates to fluconazole was done by disk-diffusion method. Results: The rate of culture positive cases of VVC was 46.3%. Most number of cases belonged to the age group of 18-27 years (43.6%). Adhibasi-janajati and married women were most commonly affected (55.9% and 62.3% respectively). Abnormal vaginal discharge with burning and itching were the most common symptoms. C. albicans accounted for the majority of the isolated Candida spp. (57.8%), followed by C. glabrata (26.5%) and C. tropicalis (9.8%), C. krusei (3.0%), C. parapsilosis (2.0%) and C. keyfr (0.9%). A total of 34.3% of isolated Candida spp. were resistant to fluconazole. Conclusion: Both C. albicans and non-albicans Candida species were responsible for acute cases of VVC and RVVC. A majority of nonalbicans Candida species were found to be resistant suggesting rise in their prevalence and resistance to fluconazole.